BẢO MẬT LỚP VẬT LÝ TRONG MẠNG KHÔNG DÂY - Trương, Tiến Vũ (Trường Đại học Đà Lạt, 2023)
In this paper, we present an approach for wireless security based on physical layer. The basic principle of physical layer secrecy (PHY Secrecy) is ensuring secure information transmission in the the system that consists of illegal receiver without using any coding solution on application layer. Applying this approach, we evaluate the physical layer secrecy performance of MISO (Multi Input-Single Output) system that consists of double antennas transmitter and single antenna receiver in the presence of a single antenna passive eavesdropper’s over heterogeneous fading channels Rayleigh/Rician. We evaluate, analyse secrecy capacity, existence probability of secrecy capacity and secrecy outage probability and verify the numerical results with Monte-Carlo simulation results. Our results have presented the utility of using physical layer secrecy to enhance the secrecy performance of wireless networks.